Use of cooled bull semen as a strategy to increase the pregnancy rate in fixed-time artificial insemination programs-case report - Crespilho, Andre Maciel; Papa, Frederico Ozanam [UNESP]; Santos, Marcos de Paula; Sá Filho, Manoel Francisco de (Science Publications, 2012)
Semen cryopreservation is still considered suboptimal due to lower fertility when compared to fresh semen. The reasons for the loss of fertility are various and related to irreversible damage caused to the cells during the freeze-thaw process. An alternative to conventional cryopreservation represents the use of chilled bull semen, preventing the damage associated with freezing, thereby guaranteeing greater sperm viability. The aim of this study was to describe the use of cooled bull semen as a strategy to increase the pregnancy for Fixed-Time Artificial Insemination (FTAI) of Nellore (Bos indicus) cows. One ejaculate of a select Nellore bull obtained by electroejaculation was used; the semen sample was fractioned into two aliquots: one diluted in Botu-Bov® extender containing 6.4% glycerol for cryopreservation (BB-F, frozen group) and one diluted in the same extender, free from cryoprotectants and used for cooling (BB-C, cooled semen group). The samples in the BB-C group were chilled to 5°C using an isothermic box and maintained for 24 h prior to use. A total of 349 lactating Nellore cows (70-90 days after birth) were synchronized by the insertion of a progesterone releasing device (1.0 g) and estradiol benzoate (2.0 mg i.m.) on a random day of the estrous cycle (Day 0); FTAI was performed 44-48 h after the removal of the device. The pregnancy rates were 45.71 and 61.49% (P<0.05), respectively, for the cryopreserved or chilled bovine semen groups. In conclusion, the use of bull semen cooled for 24 h represents an alternative to conventionally cryopreserved semen, as determined by the increase the pregnancy per artificial insemination in bovine herds. © 2012 Science Publication.
Keywords: Artificial insemination; Bull; Cooled semen; Pregnancy; Reproduction